(untitled) (Bangladesh Journal of Animal Science, 2012)
Dairy animal rearing is an inseparable and integrated part of smallholder subsistence farming system. Dairy cattle production in the country is characterized by low productivity levels due mainly to genetic and nutritional constraints. Unless feeding management is improved these animals may be limited to fully express their potential genetic superiority. It is fundamental approach to provide good quality diets to dairy cattle in sufficient amount to maximize production. Dairying provides women with a regular daily income vital to household good security and family well being. Quantitative and qualitative shortage of feeds and fodder affects the performance of milking animal. Local cows yield on average 1.5 Lit. milk per day against 5-8 Lit. in cross bred cows, require better feeding mainly concentrates, which is not available to the farmers at the affordable prices. But income of farmers can be increased up to two fold (Tk.58 vs 115) by rearing cross bred cows. Since feed cost is becoming the most important factor in livestock production, increasing self sufficiency in feed production will be an important factor in future development programs. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9914 BJAS 2009; 38(1-2): 67-85